2014
DOI: 10.1016/j.jsat.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Brief motivational enhancement intervention to prevent or reduce postpartum alcohol use: A single-blinded, randomized controlled effectiveness trial

Abstract: Aims To assess the effect of brief motivational enhancement intervention postpartum alcohol use. Design Single-blinded, randomized controlled effectiveness trial in which pregnant women were assigned to receive usual care or up to 5 face-to-face brief motivational enhancement sessions lasting 10–30 minutes each and occurring at study enrollment, 4 and 8 weeks after enrollment, 32 weeks of gestation, and 6 weeks postpartum. Setting Large, urban, obstetrics clinic. Participants Women who were ≥18 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…For postpartum alcohol use, both single BI during the postpartum period (Ondersma et al, 2016) and 4 antenatal plus one postpartum motivational enhancement session (Rubio et al, 2014) did not show significant effects compared with the control groups receiving usual care. Additionally, studies on computer‐delivered BI, a relatively new mode of BI, were either feasibility and acceptability or pilot studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For postpartum alcohol use, both single BI during the postpartum period (Ondersma et al, 2016) and 4 antenatal plus one postpartum motivational enhancement session (Rubio et al, 2014) did not show significant effects compared with the control groups receiving usual care. Additionally, studies on computer‐delivered BI, a relatively new mode of BI, were either feasibility and acceptability or pilot studies.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, it is important to note that 3 of the 15 BI studies, which showed no significant treatment effects, were either feasibility or pilot studies. The majority of studies employing BI demonstrated reduced external validity scores on study quality assessment; specifically, blinding to treatment assignment was only demonstrated by 5 studies (Fleming et al, 2008; Ondersma et al, 2015, 2016; Rubio et al, 2014; Tzilos et al, 2011). Treatment fidelity was however demonstrated by the majority of studies (Armstrong et al, 2009; Chang et al, 1999; Handmaker et al, 1999; Marais et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fleming and colleagues evaluated a four-session series of postpartum motivational sessions, delivered during routine medical care, and found significant reductions in several drinking-related outcomes [10]. In contrast, Rubio and colleagues examined a five-session, primarily during-pregnancy motivational intervention and found small but not significant effects on postpartum alcohol use [11]. Such findings should be considered in light of the much larger literature using general samples of adults with unhealthy alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Although very limited in number and methodological quality, there is some evidence on brief intervention for heavy drinkings such as psychiatric outpatient setting, [45] community-based counselling centres, sexual health clinics, and antenatal care and postpartum care settings [46][47][48][49]. However, none of the studies reported a superior benefit for brief intervention as compared to routine care [50,51].…”
Section: Alcohol Brief Interventions In Miscellaneous Settingsmentioning
confidence: 99%